PENGEMBANGAN MEDIA VIDEOSCRIBE UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPAS TENTANG PERUBAHAN WUJUD BENDA MENGGUNAKAN MODEL COOPERATIF LEARNING DI SDN 060925 MEDAN - Ahmad Landong; Tarisah Sandrina; Nur Jannah Pohan; Try Ayunda Tasya; Sri Rahayu Murwaningsih; Paujiah Nasution; Rika Eliza Matondang; Sari Sarumaha; Novia Rovalanda Sembiring (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education can run well with guidelines and guidance in its implementation, namely the curriculum. It can be said that the curriculum is the heart of education, like the current curriculum, namely the Independent Learning curriculum. However, the results of initial observations carried out at SD 060925 Medan were that there were still many students who lacked focus in the learning process because the learning media were not interesting so students' interest in learning was low. So, the solution to the problem above can be done by determining the right learning media, namely using video writing media. The aim of this research is to produce a video scribe learning media while testing the validity, practicality and effectiveness of the resulting product, so that it is suitable for use. The type of research carried out was Research and Development (R&D). Data on the level of effectiveness of the videoscribe media can be measured from the level of students' mastery of the material being taught with the results showing that the percentage of learning outcomes for class IV students at SDN 060925 Medan was 100% in the very effective category. Students are said to be complete if they have a score above or equal to the KKM score of 75. So the percentage of student learning outcomes of 100% is in the very effective criteria of 100% in the very effective category. Students are said to be complete if they have a score above or equal to the KKM score, namely 75. So the percentage of student learning outcomes of 100% is in the very effective criteria.